Uganda : Does Information Matter? - World Bank (Washington, DC, 2015)
Uganda has made important progress toward meeting the Millennium Development Goals, including halving its poverty rate to around 20 percent from more than 50 percent in the early 1990s. But healthcare, especially in the rural areas, is generally of poor quality. Small clinics, known as dispensaries, provide care to Uganda’s rural residents. The clinics offer preventive, maternity, and outpatient care, as well as lab services. All services are supposed to be free. Six to 10 people staff most clinics, including a trained medical worker, nurses, nursing aides, and others. But roughly 50 percent of the staff are absent on a typical day and patients’ average wait time exceeds two hours. Uganda’s health sector is decentralized and Health Unit Management Committees are supposed to be the link between the community and the facility. In practice, there’s little action on the part of the committees in terms of supervision or support. In 2005, a World Bank supported team decided to test the impact of a program to encourage rural residents to get involved in local health care delivery. Community members and health staff were given report cards grading the quality of local clinics, including information about specific clinic operations, absences and the quality of care. Meetings were facilitated between community members and health facilities to allow them to draw up a shared vision of what was needed and make a plan to achieve this. A year later, the evaluation found that the quality of healthcare improved, as reflected in lower child mortality and improved child weight. In 2007, the team expanded the project in order to test whether just bringing people together with health providers for meetings and encouraging community monitoring processes, without providing report cards, could be as effective.